La Belgique économique. - Mavaut, H. (Bruxelles : Van Sulper, 1930)
Bibliotheek E. Anseele
Dedicator: Mavaut, H., dedicatee: Anseele, Edward (sr.)
Overdruk uit "Le Flambeau", november 1930
Frans
Brochure